(untitled) (Marketing Journal, 2025)
This article explores the international marketing strategies of the multinational corporation Apple, analyzing their role in achieving global market success. It emphasizes key approaches such as product differentiation, premium pricing, brand loyalty, and stand ardized global strategies. The paper also investigates psychological marketing tools used by Apple to influence consumer behavior. The applicability of these strategies to local enterprises is discussed in depth.